2015
DOI: 10.1371/journal.pone.0128605
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Features of Brain-Derived Neurotrophic Factor in Mood Disorders

Abstract: ObjectivesBrain-derived neurotrophic factor (BDNF) plays important roles in neuronal survival and differentiation; however, the effects of BDNF on mood disorders remain unclear. We investigated BDNF from the perspective of various aspects of systems biology, including its molecular evolution, genomic studies, protein functions, and pathway analysis.MethodsWe conducted analyses examining sequences, multiple alignments, phylogenetic trees and positive selection across 12 species and several human populations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The conservative structure of BDNF, with 85.9–100 % identity among genes of various vertebrates and humans, determines its physiological function, to a large extent independently of the stage of phylogenetic development (Yeh et al. 2015 ). BDNF is a member of the neurotrophin family, which also includes nerve growth factor (NGF), neurotrophin 3 (NT3), and neurotrophin 4 (NT4) (Hohn et al.…”
Section: Introductionmentioning
confidence: 99%
“…The conservative structure of BDNF, with 85.9–100 % identity among genes of various vertebrates and humans, determines its physiological function, to a large extent independently of the stage of phylogenetic development (Yeh et al. 2015 ). BDNF is a member of the neurotrophin family, which also includes nerve growth factor (NGF), neurotrophin 3 (NT3), and neurotrophin 4 (NT4) (Hohn et al.…”
Section: Introductionmentioning
confidence: 99%
“…Like other neurotrophins, a pro-BDNF was cleaved to a mature-BDNF (m-BDNF) in the endoplasmic reticulum or in other way, pro-BDNF is released into the extracellular environment and cleaved by plasmin (Barker 2009). Some studies have demonstrated that the pro-BDNF and the m-BDNF had opposite biological potentials (Barker 2009;Yeh et al 2015), while other studies indicated that pro-BDNF and m-BDNF collaborated with each other in the neurodegenerative diseases (Fahnestock et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the linkage of BDNF with bipolar disorder have reported both positive [66,67] and negative findings [68,69], meaning its importance is open to question. Yeh, Kao and Kuo used a range of computational approaches to marry GWAS with the known BDNF activity network [70]. They concluded that no significant association was observed between BDNF and affective disorders in the majority of genomic studies, although a consistent relationship between plasma/serum BDNF and affective disorders was reported.…”
mentioning
confidence: 99%
“…and NOS3, and a clear association between their biological networks and affective disorders emerged [70]. Hence, by using a systems approach to expand a query from a single protein to several hundred interacting proteins (the interactome), novel biological insights were gained.…”
mentioning
confidence: 99%
See 1 more Smart Citation